Pengaruh pendekatan realistic mathematics education (RME) terhadap pemahaman konsep bangun datar peserta didik kelas III SD gugus diponegoro - Dzikri, Fais Ahla; Riyadi, Riyadi (Universitas Sebelas Maret, 2026)
This study aims to determine the effect of the Realistic Mathematics Education (RME) approach on third-grade elementary students' conceptual understanding of plane figures. The low level of mathematical understanding among students, particularly in geometry, serves as the background for this research. A quantitative method with a quasi-experimental design using a non-equivalent control group was employed. The sample consisted of 67 third-grade students divided into experimental and control groups. Data were collected using pretest and posttest essay-based assessments and analyzed through an independent sample t-test. The result showed a significance value of 0.046 (< 0.05), indicating a significant difference between the two groups. Students in the RME group achieved higher average scores than those in the control group. The RME approach proved effective in enhancing conceptual understanding by presenting real-life contexts, engaging students actively, and supporting the cognitive development of elementary learners. Moreover, RME promotes critical thinking and problem-solving through a gradual mathematization process from concrete to abstract. Based on these findings, RME is recommended as an alternative mathematics teaching strategy that is meaningful and enjoyable for young learners.